2020
DOI: 10.2147/cmar.s232294
|View full text |Cite
|
Sign up to set email alerts
|

<p>LncRNA WT1-AS Downregulates Survivin by Upregulating miR-203 in Papillary Thyroid Carcinoma</p>

Abstract: Objective: This study aimed to assessment the functions of lncRNA WT1-AS in papillary thyroid carcinoma (PTC). Methods: Expression levels of WT1-AS in PTC and non-tumor tissues from 66 PTC patients were measured and compared by performing qPCR and paired t test, respectively. Cell proliferation (CCK-8) assay was performed to evaluate the effects of the overexpression of WT1-AS, miR-203 and survivin on the proliferation of IHH-4 (a human PTC cell line) cells. Results: We found that WT1-AS was significantly down… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Considerable evidence has shown that WT1-AS is associated with the progression of several types of tumors through regulating cell proliferation and metastasis. 20,21 Besides, WT1-AS is downregulated in NSCLC tissues and in negative correlation with poor survival of NSCLC patients. 17 However, the functions of WT1-AS in NSCLC cells are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence has shown that WT1-AS is associated with the progression of several types of tumors through regulating cell proliferation and metastasis. 20,21 Besides, WT1-AS is downregulated in NSCLC tissues and in negative correlation with poor survival of NSCLC patients. 17 However, the functions of WT1-AS in NSCLC cells are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ITPK1-AS1 expression could predict gastric cancer patients’ survival ( Hu et al, 2019 ). WT1-AS has been characterized as a tumor-suppressive lncRNA in several cancers including cervical squamous cell carcinoma ( Zhang et al, 2019 ), gastric cancer ( Du et al, 2016 ), papillary thyroid carcinoma ( Le et al, 2020 ), non-small cell lung cancer cell ( Jiang et al, 2020 ), and hepatocellular carcinoma ( Lv et al, 2015 ). Besides, WT1-AS can regulate WT1 on oxidative stress injury and apoptosis of neurons in Alzheimer’s disease via inhibition of the miR-375/SIX4 axis ( Wang Q. et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to miRNAs, lncRNAs have been documented to execute their function either as tumor suppressors or oncogenes or display cellular context-dependent functions ( Table 1 ). WT1-AS was inversely associated with the overall survival of patients with TC ( 97 ). Overexpression of lncRNA HOTAIR is correlated with worse clinical outcomes in TC ( 142 ).…”
Section: Clinical Relevance Of Lncrna In Tcmentioning
confidence: 99%